The Association Between Magnetic Resonance Imaging Disc Pathology and Provocative Discography at the Lumbar Level. Issue 1 (January 2021) - Waldrop, Greer; Trent, Graham; Dagher, Azar P.; Reinig, James; Thompson, Kerry J.
Abstract : Objective: The objective of this study was to show that degenerative lumbar magnetic resonance imaging findings variably increase discography pain by level. Methods: Lumbar discography and magnetic resonance imaging of 736 patients were retrospectively reviewed. Univariate/multivariate logistic regressions calculated the odds ratio (OR) (95% confidence interval, P < 0.05). Results: L3-4 multivariate regression OR for a degenerative disc is 9.9; for bulge, 10.9; for annular tear, 38.9; for herniation, 51.5; and for degenerative facet, 2.158. Endplate changes were not significant. L4-5 OR for a degenerative disc is 4.52; for bulge, 13.74, for tear, 19.13; for herniation, 28.65; for endplate edema, 3.47; and fatty change, 3.84. Degenerative facet ORs were not significant. L5-S1 OR for a degenerative disc is 6.86; for bulge, 5.65; for tear, 40.56; and for herniation, 77.98. Endplate changes and degenerative facet OR's were not significant. Conclusions: Advancing degeneration increases pain at L5-S1 followed by L3-4. Endplate signal is significant only at L4-5.